Effect of short PSG peptide fragments on the cytokine profile in Wistar rats during allogeneic transplantation in vivo - V. P. Timganova; M. S. Bochkova; K. Yu. Shardina; S. V. Uzhviyuk; E. V. Gutina; M. B. Rayev; A. V. Lyubimov; S. A. Zamorina (Медицинская иммунология)
Pregnancy-specific beta-1-glycoprotein (PSG) is a protein with pleiotropic biological effects, particularly immunoregulatory and immunosuppressive potential. The use of recombinant PSG may exert therapeutic effects in experimental animals with induced autoimmune diseases. Recently, a search for the biological effects of short linear motifs (SLiMs) has become a new strategy for designing the pharmacological compounds. Tetrapeptide regions have been identified in the primary structure of several PSGs: YQCE, YECE and YACS, these SLiMs exhibit immunomodulatory activity. The aim of our study was to evaluate the prospectives for usage of PSG peptide fragments as pharmacological agents to modulate transplant immunity. We used an original model of host-versus-graft response in male Wistar rats transplanted with bone marrow, without prior conditioning treatment of recipients. We used a cocktail of the PSG peptide fragments administered to Wistar rats in the course of allogeneic bone marrow transplantation (BM) in dynamic manner, evaluating the cytokine profile as an integral index of immune response. Cytokine levels were determined by multiplex method using Bio-Plex ProTM Rat 23-Plex kit. Statistical processing of the data was performed by means of two-way analysis of variance and Tukey’s post hoc test for multiple comparisons. We have found that the levels of pro-inflammatory cytokines (IFNγ, IL-1α, IL-1β, IL-18), as well as the contents of G-CSF, GM-CSF and IL-7 were increased in the animals injected with BM only. In the group of animals injected with BM + PSG peptides, an increase in IFNγ, IL-6, TNFα was observed, which decreased by the end of the experiment. Increased levels of antiinflammatory cytokines IL-4 and IL-13 were detected in blood serum of the animals on day +14. Moreover, administration of PSG peptides also led to increase in IL-2, M-CSF, MCP-1, and RANTES levels on day 14 from the beginning of the experiment, and to a gradual decrease in their levels till the end of the experiment. Meanwhile, control group showed a marked tendency for increase of these and other cytokines. Thus, it was shown that the use of PSG peptides upon development of immune response to BM allograft may promote a return to normal levels for the most cytokines studied, thus presuming the immunopharmacological potential of these peptides. The obtained data can be used to develop a pharmacological preparation of the studied peptides to correct the imbalance of immune system.